KNOWLEDGE MANAGEMENT MATURITY AT DANA PENSIUN TELKOM (The Indonesian Journal of Business Administration, 2019)
Dana Pensiun Telkom (Dapen Telkom) is a company managing and providing pension funds to employees of PT. Telekomunikasi Indonesia. Today, Dapen Telkom is experiencing problems due to the failure of knowledge management in the company. This causes the performance of the company to experience fluctuations in the last five years, due to the occurrence of information gaps within the organization. The value of knowledge management proves it in the Kriteria Penilaian Kinerja Unggul (KPKU), which is still relatively low and has not shown signs to the company's vision. Besides, the company is currently at risk of losing knowledge assets, because 31% of top management employees will retire. The need for measuring the maturity level of knowledge management that has occurred in the company so that the writer can provide advice to develop knowledge management. The qualitative approach uses in-depth interviews about knowledge management within the company with six respondents. The quantitative approach uses seven categories from the APO Framework. From the results of the analysis that has been done, knowledge management is at level three, namely: expansion. Where companies have carried out knowledge management functions, but only occur in several departments. Knowledge management has not been massive in all departments within the business. After the author makes a root cause of the problem that arises, then suggests that the company takes the initiative towards the knowledge management program. Namely through; leadership, KM team, knowledge cafe, project/training lesson learned, and digital learning.Keywords: Pension Fund,Kowledge Management, Knowledge Loss, Knowledge Conversion, Maturity Assesment, APO Framework